India - A Preferred Destination for IVF Treatment - Utkarsh M Bansode (Global Journal of Fertility and Research - Peertechz Publications, 2017)
In this the major focus is on country India which is chosen as best destination for infertility related issues .what are the major factors for selecting India for IVF Treatment .Let us go through the different factors by understanding the cause of each factor in depth. Let us first understand the term IVF why it is followed and why India is given first preference for IVF Treatment. IVF is the process of fi nding the cause of infertility in human that differs in gender. In this process an egg and frozen sperm is combined together and then strong embryo is transferred into the uterus.